Senses of justice after managed retreat in New York city - Olivotto, Veronica; Wijsman, Katinka; McPhearson, Timon (Frontiers in Climate, 2025)
Sea level rise and increasing frequency and intensity of coastal storms are driving the need for managed retreat and relocation for at risk coastal populations. Managed retreat through voluntary buyouts is typically studied either from the perspective of the buyouts’ process or focused on those who leave, but little attention is given to who and what is left behind. How do buyouts impact those staying behind, and their senses of justice? We examine this question for the low-lying majority-minority neighborhood of Edgemere, Queens in New York City where Superstorm Sandy buyouts and a long history of failed urban renewal have led to large amounts of vacant land. This study analyzes ongoing and intersectional conditi ons of residents’ flood vulnerability. It grounds this analysis in 18 in-depth interviews with local residents capturing their perceptions of vacant land and its reuse, flood risk and neighborhood needs. The analysis is complemented with field observations, semi-structured interviews with city agencies involved in resilience planning initiatives and analysis of historical urban planning and open space plans in this area. Findings reveal the importance of elevating residents’ understanding of place to inform possible land uses after retreat in historically disinvested neighborhoods. Furthermore, they reveal both the injustices of and attachments to living in flood prone, disenfranchised coastal neighborhoods. They also show how these experiences entangle with the citywide housing crisis. In conclusion, if retreat and post-buyout efforts aspire to be just, they need to center how past and present contextual injustice shapes the relationships between distributive and recognitional injustice.